Nilai Tambah Kakao Fermentasi pada Unit Usaha Produktif (UUP) Tunjung Sari Br. Cangkup, Ds. Pesagi, Kec. Penebel, Kab. Tabanan - YASTIKA, I WAYAN ARI; USTRIYANA, I NYOMAN GEDE; YUDHARI, DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Improved Analysis of Value Added Cocoa Fermentation In Business Units productive ( UUP) TunjungSari The purposeof this study was to determine the cocoa fermentation process , the determination of the value -added processing and obstacles encountered in increasing the added value of cocoa fermentation in productive Business Unit (UUP ) Tunjung Sari . The study was conducted in January 2012 , located at the Banjar Cangkup , Pesagi Village , District Penebel , Tabanan regency . Location selected (purposive ). Data collection methods used were observation , interview and documentation . Selecting respondents (purposive ) based on the duties and responsibilities ofeach.The analysis method used isdescriptive analysis method . This studyis descriptive qualitative . The primary data obtained fromdirect observationan dinterviews , and secondary data obtained from the study of literature . Based on the survey results revealed that the cocoa fermentation process include:(1)the procurement of raw materials , (2)bean sorting , (3)fermentation , (4)drying , (5)packing and (6)of storage.The results showed that the fermentation of raw material purchase cocoain 2011 amounting to Rp1,207,205,000 , while sales of Rp 2,062,775,000 . The added value obtained from the fermentation of cocoa processing Rp 2628.3/kg with a margin of 28.79 %. From the above results should be productive Business Unit(UUP ) SariTunjung more attention to quality , taking into account theamount of processing . Keyword : a nalysis , v alue a dded , c ocoa f ermentation